Meru couples planar cell polarity with apical-basal polarity during asymmetric cell division - Banerjee, Jennifer J (eLife, 2017)
Polarity is a shared feature of most cells. In epithelia, apical-basal polarity often coexists, and sometimes intersects with planar cell polarity (PCP), which orients cells in the epithelial plane. From a limited set of core building blocks (e.g. the Par complexes for apical-basal polarity and the Frizzled/Dishevelled complex for PCP), a diverse array of polarized cells and tissues are generated. This suggests the existence of little-studied tissue-specific factors that rewire the core polarity modules to the appropriate conformation. In Drosophila sensory organ precursors (SOPs), the core PCP components initiate the planar polarization of apical-basal determinants, ensuring asymmetric division into daughter cells of different fates. We show that Meru, a RASSF9/RASSF10 homologue, is expressed specifically in SOPs, recruited to the posterior cortex by Frizzled/Dishevelled, and in turn polarizes the apical-basal polarity factor Bazooka (Par3). Thus, Meru belongs to a class of proteins that act cell/tissue-specifically to remodel the core polarity machinery. DOI: http://dx.doi.org/10.7554/eLife.25014.001